Analisis Penerimaan Usaha Kenari di Desa Onto Kecamatan Bontomatene Kabupaten Kepulauan Selayar - Rini, Rini Pratiwi; Andi Mawaddah Zakiyah; Sri Arfiani Rahim Sila; Suhartono; Ulfa Adzkia (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
Walnut plants are a type of Multi Purpose Tree Species (MPTS) plant from Maluku. This plant has many benefits, especially as a food ingredient, but walnut commodities are still classified as by-products so it is difficult to obtain the production data. The study aimed to determine the amount of income walnut farmers receive to achieve an increased community economy. Revenue data was obtained from the physical amount of the product multiplied by the prevailing price. The study results showed that the potential for walnuts in Selayar Regency reached 273.19 tons, mainly in Onto Village, which reached 29.24 tons with a land area of 41 Ha. The selling price of walnuts is quite expensive, namely IDR 60,000 / kg. On average, if farmers have 1 ha of land, the farmer's income per year is around IDR 21,600,000. The findings suggest that walnuts are a favored crop in Onto Village, underscoring their role in enhancing community income